Food waste and insecurity during COVID-19 pandemic: analysis of a popular restaurant in São Paulo - SP (Research, Society and Development, 2022)
The objective of this study was to evaluate food waste during COVID-19 pandemic, based on the analysis of food rest at a popular restaurant in the city of São Paulo, whose target audience are people facing socioeconomic vulnerability. This is a cross-sectional, quantitative study carried out in a popular restaurant in São Paulo/SP, for low-income, socially vulnerable and/or homeless people. Data collection regarding the rest-intake index was carried out for 5 different and random days from March 04th to 15th, 2022, with 100 costumers each day, measuring the portion of the meal, the total weight of distributed food and the total weight of rest food. As a result, a total average of food rest was observed amounting to 2,4kg, percentage of rest-intake around 4,4% and average per capita rest food at 24,0g. The ratio of food waste at this popular restaurant was considered low, however more studies must be carried out to observe and clarify in more detail the reasons for such results, in addition to outlining strategies to reduce the ratio of food waste, contributing to a higher food security for the population, mainly the most vulnerable slices.